Efecto de la adición de zanahoria, maíz y avena como pigmentantes naturales para la mejora integral del rendimiento de los pollos de engorde durante la etapa final - Olea Gómez, Melany Nicole (2025)
World poultry production has experienced significant growth in response to increased food demand due to population growth. The present research work aimed to evaluate the effect of adding a mixed diet with natural pigments for the comprehensive improvement of the meat quality of broiler chickens during the final stage. The research was developed at the Faculty of Agricultural Sciences of the Technical University of Babahoyo. 150 birds were evaluated. The conclusions determined that the addition of carrot, corn and oats as natural pigments do not cause an effect on the comprehensive improvement of the performance of broiler chickens during the final stage; the variable accumulated feed consumption (kg) and feed conversion stood out with the treatments in which commercial feed was used without the addition of natural pigments; the greatest weight increase in broiler chickens in the fourth and fifth week was obtained with the treatment in which Oats + Carrot was added, however, this decreased in the final weight variable; Regarding carcass performance, the treatment used (Bake + Yellow Corn) stood out and the skin tone with the Roche colorimetric scale (DMS) recorded that the birds that were fed with only feed without natural pigments obtained the jonquil tone; when feed + Yellow Corn was used, it showed the narcissus yellow tone and Oats + Carrot showed a yellow tone.